2015
DOI: 10.1007/s00426-015-0654-0
|View full text |Cite
|
Sign up to set email alerts
|

Time perception and the experience of agency

Abstract: In the current study, we investigate whether sense of agency over an effect coincides with the perceived time of the effect that occurs either at its usual time or earlier or later than usual. One group of participants usually perceived an action effect immediately after the action, another group delayed by 250 ms. In test blocks the effect stimulus was sometimes presented earlier or later than usual. Participants judged either the degree of experienced agency over the effect or whether the effect had appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…The effect might be attributed to external sources, instead of to the causing action, especially if users are not used to immediate machine responses. Previous results showed more sense of agency for effects occurring frequently after their specific delay (Haering & Kiesel, 2015, 2016 as well as faster response times to these effects .…”
Section: Discussionmentioning
confidence: 78%
“…The effect might be attributed to external sources, instead of to the causing action, especially if users are not used to immediate machine responses. Previous results showed more sense of agency for effects occurring frequently after their specific delay (Haering & Kiesel, 2015, 2016 as well as faster response times to these effects .…”
Section: Discussionmentioning
confidence: 78%
“…In other words, the action and its consequence are perceived as being closer to each other than they actually are. This effect has also been called intentional binding 3 and it is the subject of intense theoretical debate 9 10 : Some researchers have argued that it is causation, rather than intentionality, that is critical in producing this phenomenon 11 , while others contend that both intentionality and causality are critical 12 . Interestingly, it has also been shown that when people get used to a certain delay between their actions and their effects, presenting the effects with a shorter delay may even reverse the perception of the events, so that the tone might be perceived as occurring before the action 13 .…”
mentioning
confidence: 99%
“…Some studies investigated the temporal integration window during the elicitation of agency and they found that a delay between an action and its feedback can generate the sense of agency 41,42 . The temporal integration window of perceived agency is even recalibrated along with perceived sensorimotor simultaneity during recalibrated training 11,12,14,15,43 , and sense of agency can in turn influence temporal recalibration 44,45 . However, some limitations should be noted, and these need to be resolved in our future work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is suggested that synchronous movements may elicit these senses through temporal synchronous perceptions during interpersonal synchronization. That is, temporal synchronous perception could affect the multisensory integration of human perceptions, as the senses of agency [10][11][12][13][14][15][16] and ownership 13,[17][18][19][20] were generated by multisensory integration. In contrast, if mirror-symmetrical movements elicit these senses, the visual information on mirrored movements during interpersonal synchronization could affect the multisensory integration of human perceptions to induce elicitation.…”
mentioning
confidence: 99%